Effect of Garlic Paste Addition on the Fatty Acid Profile and Oxidative Stability of Shrimp Analogue Fortified with PUFA-rich Fish Oil During Frozen Storage at -20°C: Oxidative Stability of PUFA Fortified Frozen Stored Shrimp Analogue - S., Remya; K. R. Sreelakshmi; C. O. Mohan; S. Basu; G. Venkateshwarlu (Fishery Technology, 2024)
The current study aimed to develop a shrimp analogue product fortified with PUFA-rich fish oil and improve its oxidative stability during five months of frozen storage at -20°C. The shrimp analogue, prepared from pink perch (Nemipterus japonicus) surimi, was added with 2.5% cod liver oil and 4% starch (1:1 ratio of native and modified potato starch). The product was prepared with and without antioxidants. Garlic (Allium sativum L.) paste (2 g/100 g surimi) as the natural antioxidant, and butylated hydroxyanisole (BHA) (0.02% of the weight of the cod liver oil) as the synthetic antioxidant. The lipid oxidation indices such as PV and TBARS were monitored monthly. Garlic paste significantly (p≤ 0.05) reduced lipid oxidation compared to the control, while BHA was the most effective antioxidant. The fatty acid profiling by GCMS revealed that the predominant fatty acid in all three samples was oleic acid (18:1, n-9), the monounsaturated fatty acid (MUFA). The dominant saturated fatty acids (SFAs) were myristic acid (14:0), palmitic acid (16:0), and stearic acid (18:0) while important n-3 PUFAs were EPA (20:5, n-3), DHA (22:5, n-3) and α-linolenic acid (18:3, n-3). After 150 days of frozen storage, the ΣPUFA/ΣSFA ratio was highest in BHA (1.03) and garlic (0.90) added samples, compared to control (0.85). The addition of garlic positively influenced the fatty acid profile and reduced lipid oxidation leading to superior nutritional quality for the shrimp analogue.